Depressive symptoms in older adults awaiting cataract surgery - Palagyi, A.; Rogers, K.; Meuleners, Lynn; McCluskey, P.; White, A.; Ng, Jonathon; Morlet, Nigel; Keay, L. (Wiley-Blackwell Publishing Asia, 2016)
Background: To assess the prevalence and predictors of depressive symptoms in a cohort of older adults awaiting cataract surgery and establish threshold vision at which depressive symptoms may emerge. Design: Analysis of cross-sectional baseline data from a longitudinal cohort study of patients aged =65 years on Australian public hospital cataract surgery waiting lists. Participants: We included 329 participants enrolled October 2013–August 2015. Methods: Participants completed assessment of depressive symptoms, visual disability, quality of life, social participation and exercise frequency at least one month prior to cataract surgery. High and low contrast habitual vision was examined and systemic comorbidities noted. Main Outcome Measure: Depressive symptoms prior to first eye cataract surgery. Results: The prevalence of depressive symptoms was 28.6% (94/329). Univariate analysis identified that participants with poorer high contrast vision, reduced quality of life, greater patient-reported visual disability, higher comorbidity score and who were taking more medications were more likely to exhibit signs of depression. Greater patient-reported visual disability (P = 0.02), reduced quality of life (P = 0.003) and a higher comorbidity score (P = 0.02) remained significantly associated with depressive symptoms in the multivariable model. Depressive symptoms emerged at a visual acuity of 6/12. Conclusions: These findings demonstrate a high prevalence of depressive symptoms in older persons with cataract, emerging at modest levels of vision loss. Efficient referral processes, timely surgical management, and improved screening and coordinated treatment of depressive symptoms during the surgical wait may minimize the negative psychological effects of cataract in this already vulnerable population.